2022
DOI: 10.1002/hep.32258
|View full text |Cite
|
Sign up to set email alerts
|

Liver Transplantation for Intrahepatic Cholangiocarcinoma: Ready for Prime Time?

Abstract: Cholangiocarcinoma (CCA) represents the second-most common primary liver malignancy after HCC and has risen in incidence globally in the past decades. Intrahepatic cholangiocarcinoma (iCCA) comprises 20% of all CCAs, with the rest being extrahepatic (including perihilar [pCCA] and distal CCA). Though long representing an absolute contraindication for liver transplantation (LT), recent analyses of outcomes of LT for iCCA have suggested that iCCA may be a potentially feasible option for highly selected patients.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(40 citation statements)
references
References 90 publications
1
39
0
Order By: Relevance
“…LT might serve as a viable option in cases as follows: (I) unresectable tumor restricted to 2 cm, whilst arisen in context of chronic liver diseases; (II) unresectable tumor locally advanced within the liver (single lesion more than 2 cm, or number of lesions ≥2; without extrahepatic metastasis or macrovascular invasion), but responses to tumor down-staging modality (namely, systemic neoadjuvant therapy and/or loco-regional therapy). The items are summarized as above, which were consistent with the insights raised by other researchers (5,20,28,29). Here, the optimized combination of "maximum size of single lesion" with/without "number of lesions" remained undefined, when compared with the Milan criteria.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…LT might serve as a viable option in cases as follows: (I) unresectable tumor restricted to 2 cm, whilst arisen in context of chronic liver diseases; (II) unresectable tumor locally advanced within the liver (single lesion more than 2 cm, or number of lesions ≥2; without extrahepatic metastasis or macrovascular invasion), but responses to tumor down-staging modality (namely, systemic neoadjuvant therapy and/or loco-regional therapy). The items are summarized as above, which were consistent with the insights raised by other researchers (5,20,28,29). Here, the optimized combination of "maximum size of single lesion" with/without "number of lesions" remained undefined, when compared with the Milan criteria.…”
Section: Discussionsupporting
confidence: 78%
“…I Patients with unresectable tumor restricted to 2 cm, whilst arisen in context of chronic liver diseases (10,15,20,29). II Patients with unresectable tumor locally advanced within the liver (single lesion more than 2 cm, or number of lesions ≥2), without extrahepatic metastasis or macrovascular invasion, but with responses to tumor downstaging (namely, systemic neoadjuvant therapy and/or loco-regional therapy) (5,11,17,29). Whereas, the optimized combination of "maximum size of single lesion" with/without "number of lesions" remained undefined.…”
Section: Indicationsmentioning
confidence: 99%
“…In this study, recurrence was significantly associated with higher UICC stage and N1 status at initial LT. N1 status was also associated with impaired overall survival in multivariate analysis for oncological parameters at LT, highlighting the importance of adequate staging before LT to identify eligible patients in times of organ donor shortage. Previous studies found tumor size, histological parameters, and differentiation to be associated with a high recurrence rate [ 29 ]. We did not analyze size or detailed histological findings, as the focus of our study was the course of patients after recurrence.…”
Section: Discussionmentioning
confidence: 99%
“…Although liver transplantation is already considered a potentially feasible option for highly selected patients with pCCA and iCCA,88 89 it is to be hoped that ongoing trials will help determine if tissue biomarkers are also associated with prognosis after transplantation.…”
Section: Tissue Biomarkers For Prognosismentioning
confidence: 99%